Drug-induced liver injury: Asia Pacific Association of Study of Liver consensus guidelines - Devarbhavi, Harshad; Aithal, Guruprasad; Treeprasertsuk, Sombat; Takikawa, Hajime; Mao, Yimin; Shasthry, Saggere M.; Hamid, Saeed; Tan, Soek Siam; Philips, Cyriac Abby; George, Jacob; Jafri, Wasim; Sarin, Shiv K. (Hepatology international, 2021)
Idiosyncratic drug-induced liver injury mimics acute and chronic liver disease. It is under recognized and underrecognised because of the lack of pathognomonic diagnostic serological markers. Its consequences may vary from being asymptomatic to self-limiting illness to severe liver injury leading to acute liver failure. Its incidence is likely to be more common in Asia than other parts of the world, mainly because of hepatotoxicity resulting from the treatment of tuberculosis disease and the ubiquitous use of traditional and complimentary medicines in Asian countries. This APASL consensus guidelines on DILI is a concise account of the various aspects including current evidence-based information on DILI with special emphasis on DILI due to antituberculosis agents and traditional and complementary medicine use in Asia.